DNA topoisomerases: Advances in understanding of cellular roles and multi‐protein complexes via structure‐function analysis - McKie, Shannon J.; Neuman, Keir C.; Maxwell, Anthony (BioEssays, 2021)
DNA topoisomerases, capable of manipulating DNA topology, are ubiquitous and indispensable for cellular survival due to the numerous roles they play during DNA metabolism. As we review here, current structural approaches have revealed unprecedented insights into the complex DNA‐topoisomerase interaction and strand passage mechanism, helping to advance our understanding of their activities in vivo. This has been complemented by single‐molecule techniques, which have facilitated the detailed dissection of the various topoisomerase reactions. Recent work has also revealed the importance of topoisomerase interactions with accessory proteins and other DNA‐associated proteins, supporting the idea that they often function as part of multi‐enzyme assemblies in vivo. In addition, novel topoisomerases have been identified and explored, such as topo VIII and Mini‐A. These new findings are advancing our understanding of DNA‐related processes and the vital functions topos fulfil, demonstrating their indispensability in virtually every aspect of DNA metabolism. DNA topoisomerases are fundamental to the life of all cells due to their numerous roles in DNA metabolic processes; this includes transcription, replication, chromosome segregation, DNA repair, neurodevelopment, tumour suppression, mitochondrial DNA maintenance, and RNA processing, with new roles still being actively elucidated 50 years after their discovery.